Multi-processing feed-back decision making for scheduling gates in manufacturing system - Sefidgari, Bahram Lavi; Shamchi, Sahand Pourhassan (Trans Tech Publications Ltd ttp@transtec.ch, 2014)
This research paper investigates the optimal solution to increase the productivity of production line by the assistance of decision making and job scheduling algorithms. Through the help of FCFS algorithm which was utilized in Task Queue, as well as Multi-Level Feedback for decision making and job scheduling, the minimization of idle times during the process is expected. Moreover in case of any tardiness of machines, system immediately sends feedback to renovate the machine station. Basically the novel RFID technology (Radio Frequency Identification) is used for any data transaction between system structures, including: reading, storing and categorizing the information to each tag that attached to pieces. Besides, the software has been developed for managing the global database. All in all the current system which is based on optimal suggestion of algorithms is under implementation in the CIM laboratory of Eastern Mediterranean University. © (2014) Trans Tech Publications, Switzerland.
3rd International Conference on Manufacturing Engineering and Process, ICMEP 2014 --
Keywords: Decision making; Feed-back method; Job scheduling; Manufacturing system; RFID technology